Successful treatment of vanishing bronchus intermedius syndrome following lung transplantation - I. V. Pashkov; M. T. Bekov; R. A. Latypov; D. O. Oleshkevich; E. F. Shigaev; E. V. Lebedev; K. S. Smirnov; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2021)
The vanishing bronchus intermedius syndrome is a type of peripheral bronchial stenosis that develops in lung recipients within two to nine months after transplantation. Lack of timely diagnosis and effective treatment leads to increased mortality and poor quality of life. The clinical case presented demonstrates the successful long-term treatment of vanishing bronchus intermedius syndrome in a lung recipient using interventional bronchoscopy.